PRIVILEGED ACCESS AND QUALIA - Thomas W. Smythe (European Scientific Journal, ESJ, 2015)
In this paper I shall examine some recent literature that purports to show that sensations or qualia are not real psychological phenomena, and that we do not have privileged access to our psychological states. In particular, I shall criticize some work by Daniel C. Dennett, who has argued against the existence of qualia and privileged access to the mental. I will maintain that Dennett has not made a convincing case for eliminating qualia, and has not shown that we do not have privileged access to psychological phenomena from a first-person point of view.